(untitled) (Indonesian Sports Justice Review, 2024)
The governance of sports organizations in Indonesia is integral to ensuring fairness, transparency, and ethical standards in the country’s sports landscape. This paper examines the current state of sports governance in Indonesia, focusing on how management practices, decision-making processes, and institutional structures affect justice in sports. Through case studies of major Indonesian sporting bodies and interviews with key stakeholders, the study analyzes the ethical and legal challenges faced by sports organizations in maintaining fair play and equitable access for all athletes. It critiques the influence of political and commercial interests on sports governance and explores the role of the government, sports federations, and civil society in promoting good governance practices. The paper concludes by proposing measures to enhance accountability, such as stronger anti-corruption mechanisms, transparent selection processes for athletes, and the implementation of fair-play policies across all levels of competition.